Laser-dressing effects on the electron g factor in low-dimensional semiconductor systems under applied magnetic fields (2009)
The effects of a laser field on the conduction-electron effective Landé g factor in GaAs–Ga1−xAlxAs quantum wells and quantum-well wires under applied magnetic fields are studied within the effective-mass approximation. The interaction between the laser field and the semiconductor heterostructure is taken into account via a renormalization of the semiconductor energy gap and conduction-electron effective mass. Calculations are performed for the conduction-electron Landé factor and g-factor anisotropy by considering the non-parabolicity and anisotropy of the conduction band. Theoretical results are obtained as functions of the laser intensity, detuning and geometrical parameters of the low-dimensional semiconductor heterostructures, and indicate the possibility of manipulating and tuning the conduction-electron g factor in heterostructures by changing the detuning and laser-field intensity.